Perancangan Sistem Refrigerasi Untuk Blast Freezer Pada Kapal Ikan 200 GT - Hadi Yamlean Yohannes; Anis Mustaghfirin Muhammad; Dwijati K.R.A Daisy (Proceedings Conference on Marine Engineering and its Application, 2018)
Cold storage system of blast freezing type on 200 GT fishing vessel was designed by Shipbuilding Polytechnic Institute Surabaya (PPNS). In the last final task, the cooling system was not designed in detail so in this final project the blast freezer acceleration on vessel is carried out in detail. The design is started by calculating heat load. Then, it is continued by making pipe design, evaporator design and condenser design including compressor selection. Detailed engineering drawing on the refrigeration is also carried out to optimize the use of power and loading space. The result is the need of a compressor power is 23,27 Kw, the condenser power is 61,39 Kw and the 2 evaporator power is 18,985 Kw. The sum of condenser pipe is 360 and 2 evaporator pipes is 274 with 1,5 meters long. They are designed for the condenser and evaporator. The sum of fin evaporator is 591. The type of condenser is shell and tube. The evaporator type is finned tube. The diameter of the condenser is 423.88 mm with 1.5 meters long and the 2 evaporators are 1.5 meters x 0,3723 meters x 0,8455 meters each.